THE USE OF TEAM GAME TOURNAMENT (TGT) IN TEACHING SPEAKING ABILITY - Disti Meina (Journal of English Education Program (JEEP), 2019)
This  study  reported  on  the  use  of  Team  Game  Tournament  (TGT)  technique  in teaching speaking ability at the eighth grade of a junior high school. Team Game Tournament (TGT) technique is one of teaching technique in cooperative learning that  involves  four  stages:  teaching,  learning  team,  tournament,  and  recognition team   (Slavin,   2005).   This   study   was   conducted   in   qualitative   approach, particularly   case   study.   To   get   the   data,   the   writer   administered   classroom  observation in four sessions and interview to an English teacher and five students at the eighth grade of a junior high school in Ciamis regency. The results showed  that  based  on  classroom  observation  and  intervie w,  the  use  of  Team  Game Tournament (TGT) technique was useful to teach speaking ability;  Besides,  Team  Game Tournament  (TGT)  technique  could  make  the  classroom  activities  become  more active. Then, according to the data interview to the teacher, the teacher‟s reasons to choose Team Game Tournament (TGT) technique were the students could more increase their speaking and although Team Game Tournament (TGT) technique is team,  but  the  students  competed  with  each  other.  Hence,  based  on  classroom observation and interview to five students, the students gave positive responds in learning speaking through Team Game Tournament (TGT) technique, because the students   interested   in   Team   Game   Tournament   (TGT)   technique.   Based   on findings above, it is recommended that Team Game Tournament (TGT) technique can be used for the teacher to improve students’ speaking ability. Key   words:   teaching   speaking,   technique   in   teaching   speaking,   cooperative learning, Team Game Tournament (TGT),